Augmented Reality Advertising: Impact on Consumer Attitudes and Purchase Behavior - Faria, Gabrielle Filipa Banrezes (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Driven Marketing, specialization in Digital Marketing and Analytics